Komunikasi Organisasi Pada Karang Taruna Dalam Meningkatkan Motivasi Pemuda Kreatif Di Desa Selingsingan - Putra, Dilmai; Hidayat, Rikardo Imran; Heriniazwi, Martha (UNIVED PRESS, Universitas Dehasen Bengkulu, 2025)
This study aims to explore the organizational communication strategies implemented by the Karang Taruna (youth organization) of Selingsingan Village in fostering motivation among creative youth. Using a qualitative descriptive approach, data were collected through in-depth interviews, participatory observation, and documentation involving six informants, including the chairman, administrators, and active members of the organization. The research adopts Hersey and Blanchard's situational leadership theory as a framework, focusing on four communication styles: telling, selling, participating, and delegating. The findings reveal that the chairman's adaptive communication approach significantly enhances member engagement and motivation. Clear, open, and participatory communication practices are key to building a sense of belonging and active involvement among youth. This study recommends the continuous development of persuasive two-way communication within Karang Taruna to further strengthen youth participation in social and entrepreneurial activities.